Union Assimilation of the Ergonomics Approach and the Transformation of Social Relations - Gadbois, Charles; Villatte, Robert; Bourne, Jean-Paul; Visier, Laurent (Relations industrielles / Industrial Relations, 1995)
A large-scale project to introduce a participatory ergonomics approach into one hundred health care establishments in France was conducted by a hospital sector union. The project took the form of ergonomics training provided to union delegates to committees responsible for health, safety and working conditions. Data on the project's progress and results show that when unions had assimilated an ergonomic approach, the view that hospital actors (employees, union members, management) had of one another was modified, as were their relations concerning working condition issues. The conditions for the success, extension and durability of this approach are discussed.